Effects of potentially disruptive technology on software company's business model – Case Grid computing. (6th February 2006) - Sainio, Liisa-Maija; Porras, Jari
This paper presents a framework for analysing the effects of a new, potentially disruptive technology on a firm's business model. As a case example of the framework usage, the paper analyses the possible effects of grid infrastructure on a software company providing digital signatures. After a brief introduction of grid infrastructure and the construction of the propositional framework, it will used to estimate the disruptiveness potential of a new technology as well as the strategic importance of a new technology, both of which determine the possible amount of radical changes in a firm's business model.